Corona shape variations among nine species of Hoya - Torres, Mark Anthony J.; Demayo, Cesar G.; Siar, Simeona V. (2008)
Elliptic Fourier (EF) analysis was used to analyze the corona shapes of nine species of Hoya. Data were obtained from 239 corona samples. Chain encoded, Elliptic Fourier harmonic functions were generated based on corona boundary. A complexity index of the corona shape was computed using the variation between consecutive EF functions. Principal component analysis was used to select the Fourier coefficients with the best discriminatory power. Differences among the species were summarized in a total of nine independent shape characteristics after principal component analysis of the shape data was done. Higher shape variance (56.13%) is attributed to asymmetries in the shapes of the corona. Cluster analysis based on the shapes of the corona recognized at least three groups of corona shapes. Major differences were attributed to variation in the position of the centroid, the type of floral symmetry, and the direction and shape of the corona hoods. The results of the study clearly showed that Elliptic Fourier shape analysis is an important tool in understanding corona shape diversity in Hoya.
Keywords: Hoyas (Flower)